Effect of resin particle size and wax content on the properties of oil palm board / Jamaludin Kasim ...[et al.] - Kasim, Jamaludin; Ahmed Pakaruldin, Nik Thalah; Abu Samah, Lily Suriati; Zakariah, Mahfuzah (2008)
Homogenous layer of oil palm boards were produced using urea formaldehyde as binder. The three particle sizes (unscreened, 1.0 and 2.0 mm) used were sprayed with 8, 10 & 12% resin. A 1% wax content was also added. The oil palm board was hot-pressed at 165°C for 6 minutes. Results of the board testing showed that with increasing resin content all the mechanical and physical properties improved significantly. Bigger particles gave better mechanical but lower physical properties compared to smaller particles. With wax addition, mechanical properties were not affected while physical properties improved significantly.